Research Review and Prospect of Litchi Fruit Cracking - Xiwen LI; Haoshuang SUN; Xuequn PANG; Zhaoqi ZHANG (Guangdong nongye kexue)
Litchi is the most important high-quality fruit tree species in South China, and is also a representative fruit tree with aril as the edible part in the Sapindaceae family. However, frequent fruit cracking affects the yield and fruit quality of litchi during the growth and development, in particular for the high-value litchi varieties, such as 'Nuomici' and 'Guiwei'. Therefore, it is important to understand the factors affecting fruit cracking, and to breed crack-resistant varieties to prevent and mitigate fruit cracking, thus promote the sustainable development of litchi. In this review, we introduce the phenomenon of litchi fruit cracking and the diversity of fruit cracking types, and emphasize the distinct feature of litchi fruit cracking along the suture line. We also summarize the causes of litchi fruit cracking at different developmental stages and among different varieties from the perspectives of growth environmental conditions, litchi variety characteristics (genetics, fruit size, seed type, pericarp characteristics), and etc., and the research progress in its physiology and molecular biology including pulp TSS, calcium content, cell wall components and their associated enzymes. The review points out that although there are great differences in the susceptibility of fruit cracking among different litchi varieties, so far, we have not been able to identify the key enzymes or major genes related to fruit cracking; compared with other fruits, litchi fruit cracking has a certain degree of specificity, which is manifested in that litchi fruit cracking peaks at the stage from the green fruit stage to the color turning stage, and that the fruits always crack along the suture line with the pulp remaining intact. In the future, researches should be strengthened on the relationship between the structure of the suture line and fruit cracking in litchi fruit, and the possible influence of seed type on the susceptibility to fruit cracking.